Autochthonous fungi are central components in microbial community structure in raw fermented sausages. Issue 5 (5th November 2021) - Zwirzitz, Benjamin; Thalguter, Sarah; Wetzels, Stefanie U.; Stessl, Beatrix; Wagner, Martin; Selberherr, Evelyne
Summary: Raw meat sausage represents a unique ecological niche rich in nutrients for microbial consumption, making it particularly vulnerable to microbial spoilage. Starter cultures are applied to improve product stability and safety as well as flavour characteristics. However, the influence of starter cultures on microbial community assembly and succession throughout the fermentation process is largely unknown. In particular the effect on the fungal community has not yet been explored. We evaluate the microbiological status of four different raw meat sausages using high‐throughput 16S rRNA gene and ITS2 gene sequencing. The objective was to study temporal changes of microbial composition during the fermentation process and to identify potential keystone species that play an important role within the microbial community. Our results suggest that fungi assigned to the species Debaryomyces hansenii and Alternaria alternata play a key role in microbial community dynamics during fermentation. In addition, bacteria related to the starter culture Lactobacillus sakei and the spoilage‐associated genera Acinetobacter, Pseudomonas and Psychrobacter are central components of the microbial ecosystem in raw fermented sausages. Elucidating the exact role and interactions of these microorganisms has the potential to have direct impacts on the quality and safety of fermented foods. Abstract : We evaluate the microbiological status of four different raw meat sausages using high‐throughput 16S rRNA gene and ITS2 gene sequencing. The objective was to study temporal changes of microbial composition during the fermentation process and to identify potential keystone species that play an important role within the microbial community. Our results suggest that fungi assigned to the species Debaryomyces hansenii and Alternaria alternata play a key role in microbial community dynamics during fermentation.